Solution of Zakat Problem in Indonesia with Modification Action Research - Huda, Nurul (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
The research is aimed to identify Zakat problems encountered in Indonesia. The programs and problems were faced by Zakat institutions (OPZ) in carrying out its functions on collecting, distributing, and empowering Zakat and proposing some ideas to solve the problems. The method used was modified action research by carrying out two main steps namely problems identification and ideas proposal as the solution to the problems. The informants of the research are Zakat stakeholders including The Directorate of Zakat Empowerment, the state-supported Zakat Collecting Board (BAZNAS), the privately run institution of National Zakat Collectors (LAZNAS) of Dompet Dhuafa, Zakat practitioners, mustahiq (Zakat recipients), and muzakki (Zakat payers). The research results show that Indonesiaâs problems of Zakat which include the remaining disagreement among Zakat stakeholders on the organization models of Zakat collector and distributor, the lack of synergies employed by Zakat organizations and the limited number of Zakat officials. Besides that, can be identified that zakat empowerment and distribution are divided into two groups namely charity and empowerment. Related to the problems of Zakat institutions, the problems are the overlapping of empowerment programs among the institutions, the inaccurate data of mustahiq and muzakki, the limited number of partnerships among zakat institutions, expensive promotion model, and the limited number of professional Zakat officials. The ideas proposed for solving the above problems are the government to accommodate all the existing Zakat institutions with the approach of affiliation, the synergy among the institutions with the approach of area, collecting programs, distribution and empowerment and the standardization of Zakat officials. While the agenda of action that related to the Zakat institution problems are the compilation of mustahik and muzakiâs data through the role of mosques, the preparation of Zakat officials in the cooperation with higher education, making Zakat as a national program across departments, the collaboration with the affiliation of Indonesian preachers (IKADI) and the Board of Mosque Management (DKM).